When does it pay to be corrupt in the private sector? - Silva, Andréa Oliveira de Carvalho e (2016)
Private-to-private corruption is a phenomenon that greatly affects both firms and countries they operate in. Both contextual and behavioral aspects of decision-making under corruption risk have been previously studied. However, as the phenomenon is very complex, the field lacks on understanding the causal relationships and comprehensive models for private-to-private corruption. Given the described research opportunities, this study investigated when it pays to be corrupt in the private sector. To conduct this study, it was employed a 3x2 (risk – high, medium, low and business as usual/not as) anecdotal field experiment through the vignette technique, emulating a procurement process. This experiment had a sample of n=168; respondents had, in average, both work experience and familiarity with the B2B procurement process. Through rational choice and expected utility theory, this thesis was able to combine contextual and individual factors for decisional process, disclosing the mechanisms through what a decision-maker opt whether to act or not corruptly. It was possible to establish the causal relationship of informal social norms and the risk of punishment in corruption inclination. Also, the present study assessed variables relationships’ robustness through employing three methods to analyze the empirical data. Variables were modeled jointly through two methods: OLS and SEM-PLS. This thesis contribution to literature is threefold. In the theoretical perspective, it contributed to literature by reinforcing rational choice theory appropriateness as a framework for studying decision making under corruption risk in the private sector. In the methodological perspective, there were built integrative multiple causation models for corruption (exploring mediating relationships, also), giving an important contribution to literature, which lacked on comprehensive models for corruption and where causal relationships were mostly ignored. In the practical perspective, it contributed by questioning current policy-making strategies: it was found that, despite bounded rationality evidences, people behave mostly rationally when deciding to engage or not in corruption. However, even then we found that punitive strategies that are based on this premise are effective on diminishing corruption, which implies the fact that other policies based on moral issues should be needed to combat this problem.